How reliable is pooled analysis in political economy? The globalization welfare state nexus revisited - Bernhard Kittel; Hannes Winner (Max-Planck-Institut für Gesellschaftsforschung, 2002)
Panel data analysis has become very popular in comparative political economy. However, in order to draw meaningful inferences from such data, one has to address specification and estimation issues carefully. This paper aims to demonstrate various pitfalls that typically occur in applied empirical work. To illustrate this, we refer to the debate on the globalization-welfare state nexus. We reexamine a model by Garrett and Mitchell (2001), a leading study in this regard. Utilizing a data set of 17 OECD countries and the time period 1961 to 1993, they find evidence that globalization and partisan composition have a significant im-pact on the extent of public activity. However, because they apply a dynamic specification in levels, they do not adequately take into account both the dynamic and spherical nature of the data. In contrast, we propose an autoregressive model in first differences that is shown to perform well in statistical terms. Further, we explicitly pay attention to the time pattern of the globalization-welfare state nexus. Substantively, we find evidence that government spending is primarily driven by the state of the domestic economy. Neither partisan effects nor the international economic environment have affected public expenditure considerably. – – Panel-Daten erfreuen sich in politisch-ökonomischen Analysen zunehmender Beliebtheit. Allerdings enthalten derartige Daten einige ökonometrische Fallstricke, die wir in der vorliegenden Arbeit aufzeigen. Zur Illustration nehmen wir auf die Diskussion über den Zusammenhang zwischen Globalisierung und Wohlfahrtsstaat Bezug. Dazu greifen wir eine Arbeit von Garrett und Mitchell (2001) auf, in der gezeigt wird, dass Globalisierung und die parteimäßige Zusammensetzung der Regierung einen signifikanten Einfluss auf die Staatstätigkeit ausüben. Wir argumentieren, dass dieses Ergebnis von ihrer Modellspezifikation (dynamische Spezifikation in Niveaugrößen) getrieben wird. Demgegenüber zeigen wir, dass in der vorliegenden Datenkonstellation die statistischen Eigenschaften des Störterms ökonometrisch korrekt nur durch ein autoregressives Modell in ersten Differenzen berücksichtigt werden können. Unter Beachtung von unterschiedlichen Phasen der Internationalisierung finden wir weiters, dass die Staatsausgabentätigkeit primär durch binnenwirtschaftliche Faktoren erklärt wird. Weder Parteieneffekte noch Globalisierungsphänomene haben die Veränderung der Staatsausgaben nennenswert beeinflusst.
Keywords: 300; Staatsquote; Globalisierung; Sozialstaat; Public Choice; Panel; Schätzung; OECD-Staaten; Autokorrelation